Virtual reality in oral hygiene instruction : an immersive approach = Realidad virtual en la enseñanza de la higiene bucal : un enfoque inmersivo - Genaro, Luis Eduardo
Currently, oral health issues are increasingly been addressed and virtual reality (VR) is being used as an aid in health areas. However, there is little evidence of VR being used in preventing oral health problems. To evaluate the effectiveness of VR in oral hygiene education. Three hundred pupils, aged between 9 and 12 years, received instructions in oral hygiene by immersion VR and they gave their opinions about the performed activities. Chi-square and Fisher's exact tests were applied, with a significance level of 5%. Part perception of oral hygiene showed no statistically significant difference (P>0.550). There was an increase in the use of dental floss (P<0.001), tongue brushing (P<0.001), and tooth brushing (P<0.001). Both drawings and comments made by participants related to oral hygiene were positive regarding the project. Conclusions: The use of VR in oral hygiene instruction was effective. Most participants increased brushing and flossing frequency and produced drawings related to oral hygiene. VR is effective and should be used in dentistry for teaching and prevention , especially with children, as it presents an interactive instructional space that can be approached in a playful way. This study presents dentists with a promising alternative for changing oral hygiene habits.